Palliative whole-brain radiotherapy and health-related quality of life for patients with brain metastasis in cancer - Gao Y; Gao F; Ma JL; Zhao DL (Neuropsychiatric Disease and Treatment, 2015)
Ying Gao,1,* Fei Gao,2,* Jin-lu Ma,1 Dong-li Zhao1 1Department of Radiotherapy Oncology, First Affiliated Hospital of Xi’an Jiaotong University, 2Department of Neurology, First Affiliated Hospital of Xi’an Medical University, Xi’an, People’s Republic of China *These authors contributed equally to this work Objective: To assess the use of palliative whole-brain radiotherapy (WBRT) in the treatment of brain metastases (BMs) and to evaluate the health-related quality of life (HRQOL) of these patients.Materials and methods: We conducted a retrospective study of 46 patients with BMs who were treated with WBRT at the First Affiliated Hospital of Xi’an Jiaotong University between January 2013 and January 2015. External beam radiotherapy techniques were used to deliver 40 Gy in 20 fractions or 30 Gy in ten fractions with a 10 MV photon beam from a linear accelerator to the whole brain. Data were stored and analyzed using SPSS version 17.0.Results: Of the 46 patients, the survival time of patients in our study was 10.8±0.55 months: 11.8±0.46 months in patients with WBRT, 11.75±1.00 in patients with WBRT + chemotherapy, and 3±0.79 months in patients with supportive care, respectively (P<0.01). The HRQOL scores of all the patients were 70±1.16 (before therapy) and 76.83±1.04 (after therapy) (P<0.01). The HRQOL scores of the patients with WBRT were 72.23±0.88 (before therapy) and 78.49±0.87 (after therapy) (P<0.01). There was no central nervous system toxicity; only two (4.3%) patients were found to have BM hemorrhage. Radiation necrosis happened in one patient (2.2%).Conclusion: Effective treatment options for patients with BMs are important. WBRT was evaluated to ensure survival outcomes and QOL were enhanced after therapy for patients with BMs. Keywords: brain metastases, whole-brain radiotherapy, health-related quality of life